What matters for retirees to experience a great quality of life? - Husin, Nor Azilah; Saad, Mazni; Mariyanti, Eka; Abdul Razak, Norfadzilah (AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK, 2021)
This paper aims to identify the retirees' quality of life. A quantitative method and probability sampling technique were employed using a random selection of 210 retirees. The data is analysed using correlation and multiple regression analysis. The finding revealed that financial resources is the most influential element that influences the retirees' quality of life, followed by healthcare. Emotion does not affect their quality of life. The roles of government and private agencies such as banks, insurance, hospital, and caretakers of the retirees aware of their needs, and provide facilities to ensure a better quality of life.